The Developed Health Education Program Applying Self-care Theory in Hypertension - ศิริรัตน์ ณัทกวี; แก้วสม กัลยา (Journal of The Royal Thai Army Nurses, 2019)
The objective of the research & development was to develop health education program for hypertensive patients by applying self-care Theory. The instruments for collecting data were general information query, selfcare knowledge and behavior questionnaire. Sphygmomanometer was used. Data collected before and after using the program for 2 weeks. The samples were 30 hypertensive patients which had high blood pressure (systolic ≥140 mmHg. and diastolic ≥90 mmHg.) Data analyzed by dependent t-test. The study found that Health Education Program composed health education teaching for create knowledge and change behavior about self care on having meal, exercise, stress relief, stop or reduce smoking, alcoholic drinking, correct medication and appointed examination in order to reduce complication of the stroke. Moreover after used the program, samples had higher average scores of self care knowledge and self care behavior with statistical significance at the level of 0.05.